Photocatalytic activity of twist-angle stacked 2D TaS2 - Evgeniya Kovalska; Pradip Kumar Roy; Nikolas Antonatos; Vlastimil Mazanek; Martin Vesely; Bing Wu; Zdenek Sofer (npj 2D Materials and Applications, 2021)
Abstract The low-cost, efficient photoelectrosensitive electrodes as an alternative to expensive and complex rigid systems are yet in demand for advanced photoresponsive technology. Here, the light-induced efficiency of electrochemically exfoliated TaS2 nanosheets for hydrogen generation catalysis and photodetectors was demonstrated. Mutual twisting of the exfoliated 2H-TaS2 flakes leads to the redistribution of charge density induced by interlayer interaction of the individual nanosheets. External light irradiation on the TaS2 surface influences its conductivity making the material feasible for photoelectrocatalysis and photodetection. The TaS2-based photoelectrocatalyst demonstrates high hydrogen evolution reaction (HER) activity with the onset overpotential below 575 mV vs. reversible hydrogen electrode (RHE). The TaS2-integrated photodetector in the acidic medium represents its broadband response with the highest photoresponsivity (0.62 mA W−1) toward 420 nm light illumination. This finding will pave the way to a new realization of exfoliated twist-angle stacked TaS2 for photo-induced electrochemistry and sensing.